Vendor Business School: Empowering food vendors in urban Philippines - Prain, Gordon; Bertuso, Arma; Prain, Marco; Ricarte, Phoebe (CGIAR System Organization, 2024)
The Vendor Business School (VBS) is an innovative program of CGIAR under its Initiative on Resilient Cites. It aims to empower small food vendors by providing them with vital knowledge, skills, and resources to overcome the challenges of their daily business operations and improve their food safety measures. Currently, the VBS program is being piloted in two countries, the Philippines and Kenya. In the Philippines, CGIAR has partnered with the City Government of Quezon City to conduct the program from February to July 2024.